Policy of sustainable growth: community opinion on the regional economic development of Iskandar in Malaysia - Rabe, Noor Suzilawati; Mohamed Osman, Mariana; Bachok, Syahriah (2014)
Various regional economic strategies are included in the development plan for the region including the formation of five flagship zones as well as the budget allocation from the federal government as the development incentive. However, impacts from the economic development in contributing towards the social & environment development are questionable.